Enzymatic and Non Enzymatic Antioxidant Activity of Tabernaemontana divaricate R.Br. against DEN and Fe-NTA Induced Renal Damage in Wistar Albino Rats - Sowmya Sundaram, Gopalakrishnan Velliyur Kanniappan, Poornima Kannappan (Journal of Applied Pharmaceutical Science, 2015)
Plant derived drugs have been a part of the evolution of human healthcare for thousands of years. The present study was carried out to evaluate the antioxidant potential of ethanolic extract of Tabernaemontana divaricata on DEN initiated and Fe-NTA promoted renal damage in rats. Fe-NTA was induced after 10 days of DEN (200mg/kg body weight) initiation at a dose level of 9mg Fe-NTA/kg body weight twice a week for one month. The biochemical parameters were analyzed in serum and the antioxidant assays were carried out in kidney. Lipid peroxidation level was increased due to the administration of Fe-NTA, which caused the reduction of enzymatic antioxidant such as SOD, GPx, Catalase, G6PD, and also the non-enzymatic antioxidants vitamin C and GSH. The levels of urea, uric acid, creatinine, blood urea nitrogen were increased and protein level decreased on Fe-NTA intoxication. The secondary metabolites present in the plant increased the synthesis of antioxidant enzymes and its free radical scavenging properties helped to scavenge all free radicals thereby decreasing lipid peroxidation. Thus, the present study indicates that the plant may clinically valuable agent in the prevention of renal failure caused by DEN and Fe-NTA intoxication.
Keywords: Tabernaemontana divaricata, Diethyl nitrosamine, Ferric nitrilotriacetate, Medicinal plants, Renal damage.